Modeling and Simulation of Sensorless Speed Control of a Buck Converter Controlled Dc Motor - Bassim M. H. Jassim (Al-Khwarizmi College of Engineering – University of Baghdad, 2010)
This paper investigate a sensorless speed control of a separately excited dc motor fed from a buck type dc-dc converter. The control system is designed in digital technique by using a two dimension look-up table. The performance of the drive system was evaluated by digital simulation using Simulink toolbox of Matlab.